Q: What is the answer to 3 ( 5p - 3 ) 5 ( p - 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

20 = 4p + 5 +p 20 = 5p + 5 5p = 20 - 5 = 15 5p = 15 p = 15/5 = 3

To find the value of p, simply use addition, subtraction and division to isolate p: 5p -1 = 2p + 20 5p - 2p - 1 = 2p - 2p + 20 3p - 1 + 1 = 20 + 1 3p/3 = 21/3 p = 7 The value of p is 7.

You factor out 5 from the expression (10+5p). You get 2(5+p).

5p-10 = 50 5p = 50+10 5p = 60 Divide both sides of the equation by 5 to find the value of p: p = 12

When p = 11, 5p - 8 = 5*11 - 8 = 55 - 8 = 47

Related questions

42p-1 = 5p+4 42p = 5p+5 37p = 5 p = 5/37 p = 0.135135...

-4(3 - p) > 5(p + 1) => -12 + 4p > 5p + 5-17 > p, that is p < -17.

20 = 4p + 5 +p 20 = 5p + 5 5p = 20 - 5 = 15 5p = 15 p = 15/5 = 3

5 p/1 pound = 5 p/100 p = 1/20

5p - 3 = 15Add 3 to each side:5p = 18Divide each side by 5:p = 18/5 = 3.6

It could be 5p+3 or p(5+3)

To solve for p, set up the equation 5p + 9 = p - 3 5p = p - 12 4p = -12 p = -3 to prove the answer, substitute -3 for p and prove 5(-3) + 9 = (-3) -3 -15 + 9 = -6 -6 = -6

5p 5p

To find the value of p, simply use addition, subtraction and division to isolate p: 5p -1 = 2p + 20 5p - 2p - 1 = 2p - 2p + 20 3p - 1 + 1 = 20 + 1 3p/3 = 21/3 p = 7 The value of p is 7.

If all the terms are positive then it is: (2p+3)(p+1)

You factor out 5 from the expression (10+5p). You get 2(5+p).

5p-10 = 50 5p = 50+10 5p = 60 Divide both sides of the equation by 5 to find the value of p: p = 12